Estimation of the strength of vertical cylindrical liquid storage tanks with dents in the wall - Suleimenov, Ulanbator; Zhangabay, Nurlan; Utelbayeva, Akmaral; Azmi Murad, Masrah Azrifan; Dosmakanbetova, Aibarsha; Abshenov, Khassen; Buganova, Svetlana; Moldagaliyev, Arman; Imanaliyev, Kuanysh; Duissenbekov, Bolat (Eastern-European Journal of Enterprise Technologies, 2022)
A multi-level mathematical model was used to estimate the stressed-strained state of a cylindrical reservoir with a defect in the wall shape in the form of a dent; the concentration of stresses in the defect zone was studied. The proper choice of the mathematical model was verified; it has been shown that the engineering assessment of the stressed-strained state of the wall of a cylindrical tank with the variable thickness could employ ratios for a cylindrical shell with a constant wall thickness. The spread of values is 2‒10 %. This indicates the proper choice of the mathematical model, as well as the fact that it is possible, for an engineering assessment of the stressed-strained state of the wall of a cylindrical tank with variable thickness, to use the ratios for a cylindrical shell with a constant wall thickness. The stressed-strained state of the dent zone in the tank wall was numerically estimated, which proved the assumption of significant stress concentrations in the dent zone and indicated the determining effect on the concentration of stresses in the dent zone exerted by its geometric dimensions and its depth in particular. The concentration of stresses in the zone of dents in the tank wall was investigated in the ANSYS programming environment at different sizes of dents on the tank wall, for which two dimensionless parameters were introduced: the dimensionless radius of the dent and the dimensionless depth of the dent. Based on the results of a numerical study into the stressed-strained state of the dent zone in the tank wall, graphic dependences were derived of the stress concentration coefficient on the dimensionless depth of the dent for various values of the dimensionless radius of dents, which does not exceed 2 % of the indicator. Based on fitting the stress concentration curves on the dimensions of the dent and tank, a formula was derived for calculating the stress concentration coefficient as a function of the dimensionless radius ξ and the dimensionless depth ς of the dent. The resulting formula makes it possible, with known dimensionless parameters of the depth and radius of the dent, to determine the coefficients of stress concentration in the dented zone of the tank wall.